2011
DOI: 10.3892/etm.2011.372
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of IGFI contribute to the development of ischemic stroke

Abstract: Abstract. Insulin-like growth factor 1 (IFG1) is neuroprotective in animal models of focal brain ischemia and correlates with ischemic stroke (IS) outcome in the elderly. In this study, we investigated whether single nucleotide polymorphisms (SNPs) of the IFG1 gene are associated with the development and clinical features of IS in a Korean population. A total of 119 patients with IS and 289 control subjects were recruited. Stroke patients were classified into subgroups according to the scores of the National I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Stroke has been listed as the third leading cause of death following heart diseases and cancer in the world [ 3 , 4 , 6 ]. Ischemic stroke accounts for approximately 80 % of the total cerebrovascular diseases [ 8 ]. Therefore, the prevention and treatment of ischemic stroke has attracted a great attention from the medical profession domestically and internationally in recent years [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Stroke has been listed as the third leading cause of death following heart diseases and cancer in the world [ 3 , 4 , 6 ]. Ischemic stroke accounts for approximately 80 % of the total cerebrovascular diseases [ 8 ]. Therefore, the prevention and treatment of ischemic stroke has attracted a great attention from the medical profession domestically and internationally in recent years [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study showed that IGF1 polymorphism (rs35767) was associated with hypertension in normal weight and obesity populations [44]. Hak et al suggested that rs6214 and rs2162697 of the IGF1 gene were related with the development of stroke [12]. Genetic studies also reported that variations at IGFBP3 (rs11977526 and rs2949837) were related to the increased blood pressure [43,45].On the other hand, genetic variation at rs6032470 had lower expression levels of IGF1R genes.…”
Section: Discussionmentioning
confidence: 96%
“…A case-control study of ischaemic stroke (IS) in a Korean population observed that common variants in IGF1 genes (rs2162679 and rs6214) exhibited protective effects on the development of IS [12]. Epidemiological studies revealed that the levels of circulating IGF1 and IGFBP3 below normal range were associated with the increased morbidity and mortality from ischaemic heart disease and stroke [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al (18) found the carriers of rs6214 GG genotype have the risk of low appendicular skeletal muscle mass. IGF1 rs6214 variation wasalso found associated with Barrett esophagus (19) and the development of ischemic stroke (20). Because IGF1 plays a crucial role in hypothalamicpituitary-ovarian hormone-controlled metabolic processes, Zhao et al (21) studied rs6214 on age at menarchevariation in Caucasian women and detected the association.…”
Section: Discussionmentioning
confidence: 99%